Sistem Integrasi Proteksi & Manajemen Resiko Platform Fintech peer to peer (P2P) Lending dan Payment Gateway untuk Meningkatkan Akslerasi Pertumbuhan UMKM 3.0 - Manan, Yulianti (Universitas Ahmad Dahlan, 2019)
The MSMEs (Micro, Small and Medium Enterprises) mentioned by the government as the backbone of the Indonesian economy are also still many that have not been touched by financial services or are unbankable. Currently in line with the development of information technology in financial services, the Fintech P2P lending ecosystem and payment gateways are growing rapidly and become one of the cash less payment options, an alternative option for new types of financing due to multi-advantages; fast, collateral-free and technology-based process which is a culture of supporting MSME generation to 3.0. The Fintech P2P Lending and Payment gateway business that is oriented towards IT Base financial reporting still requires a risk management and governance system to reduce and minimize the risk of fraud, bankruptcy, default and other risks. The purpose of this research is to analyze and study innovative solutions to the Fintech business model platform related to protection system management by establishing a central and strategic role between the regulator and Fintech providers. This research uses descriptive research design by using GAP Analysis to research and develop and collaborate on innovation, especially in Fintech business operating systems.